Supply Chain Optimization and Performance of Agro-Processing Firms in Kiambu County, Kenya - Nyamweya, Patrick; Osoro, Anthony (International Journal of Supply Chain Management, 2024)
Purpose: The purpose of the study was to establish the relationship between supply chain optimization and performance of agro-processing firms in Kiambu County, Kenya. Methodology: The study used descriptive research design, where both qualitative and quantitative research was applied. The target population was 240 respondents from the concerned departments in Kiambu County, Kenya. The researcher carried census survey since respondents are manageable. The research technique was purposive random sampling techniques with different stratus. 10% (24) of the respondents were pilot tested for validity and reliability of the research instrument. Data was analyzed using descriptive statistics and inferential statistics with the help of Statistical Package for Social Science version 28 and the same was now presented in a form of tables and figures. The pilot and validity test results was over 0.7 and 0.5 respectively. The research proceeded to actual data collection with few adjustments of research questionnaire. Data was presented in form of tables. Findings: The study findings indicate that Supply Chain optimization has a broad impact on performance of agro-processing firms in Kiambu County, Kenya. The study revealed that there is a positive relationship between inventory optimization and performance of agro-processing firms, sustainability optimization influences performance of agro-processing firms, demand forecasting had a positive effect on performance of agro-processing firms and there is a positive relationship between reduced cost optimization and performance of agro-processing firms in Kiambu County, Kenya. Unique Contribution to Theory, Practice and Policy: This study was anchored on inventory theory. The study's recommendation to all firms is that the implementation of supply chain optimization and performance of agro-processing firms in Kiambu County, Kenya was a significant relationship. This study recommends that the best performance of agro-processing firms in Kiambu County, Kenya should strive to be proactive on how to perform better to retain integrity and improve transparency and accountability on performance of agro-processing firms in Kiambu County.